Prikaz velikih količin geometrijskih podatkov preko interneta - Krivograd, Sebastian (Geodetski vestnik, 2001)
The paper, we propose a scheme for the system able to transmit over the internet and visualise a huge amount of geometric data for making flight through in real time. Namely, today's communication canals with their throughput do not allow transmissions of the whole data set in a real time, and besides this, the visualisation causes some additional problems. The proposed solution consists of three steps: data preparation (presenting the data with a triangular mesh, mesh decimation, data division into several resolution models, compression of these models), data transmission from the server to a client, and receiving the data on the client's side and their visualisation. It is expected that this solution will enable to transmit and visualise huge geometric data sets in a real time.
Keywords: geodesy; geodezija; GIS; internet